Pengaruh Legum Penutup Tanah Terdapat Pertumbuhan Semai Mahoni (swietenia macrophylla) pada Tanah Marginal - Puji Lestari; Eny Faridah; Cahyono Agus D Koranto (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2017)
Indonesia has large area of marginal land including coast sandy soil and post coal mining soil areas. Reclamation process for marginal land needs long time and high cost, hence, strategic treatments are necessary to reduce both time and cost. This research aims to analyze the effects of media (coast sandy soil, alluvial deposit, and post coal mining soil) and legume over crop Centrocema pubescens on the growth of mahogany seedlings. This research was conducted at green house for 3 months using Completely Randomized Design (CRD) with 3 x 2 factorials and 3 replications. The first factor was marginal soil (three levels: coast sandy soil, post coal mining soil, and alluvial deposit as reference) while the second factor was the application of legume cover crop (two levels: apply and not apply). Variables observed were the height, diameter, biomass, and nutrient content of mahogany seedlings. The results showed that the growth of mahogany in sandy soil media is the best though nutrient content in that media is the lowest. It was caused reduction of salinity from that media. While, up to 3 months old, C. pubescens grew competitively.